Smoking dependency behaviour towards conventional & e-cigarette among selected government instituition in Indera Mahkota, Kuantan 2016 - Pasi, Hafizah; Mohd Rus, Razman; Ab Rahman, Jamalludin; Abd. Aziz, Karimah Hanim; Nasreen, Hashima E; Yusof, Muhammad Zubir (2016)
Background. Smoking is a learned behavior that is reinforced and maintained by dependence. In current studies, behavioral component of smoking dependency is less explored. We aim to describe the smoking dependency behavior towards conventional and e-cigarette among staffs of selected government institution in Kuantan, Pahang in February 2016.